Feasibility and ability of laparoscopy to predict respectability in ovarian cancer: A cohort study - Mohammed Abdelrahman; Ahmed Magdy Mahmoud*; Abdelnaser Abd Elgaber Ali; Hanan Mahmoud Fayed; Mostafa Mohammed Khodary (SVU - International Journal of Medical Sciences, 2023)
Background: Ovarian cancer is one of the deadliest cancers, as it is the seventh most prevalent type of cancer in women worldwide. Objectives: This study aimed to assess the feasibility and efficacy of diagnostic laparoscopy in predicting optimum respectability in ovarian cancer cases. Patients and methods: it was a prospective cohort study, including 38 ovarian cancer cases. The duration of the study ranged from 6-24 months. A receiver-operating characteristic (ROC) curve was constructed to assess the diagnostic ability of laparoscopy. Overall survival (OS), disease-free survival (DFS), and recurrence-free survival (RFS) were calculated using the Kaplan-Meier method. Results: of the studied patients, 30 (78.9%) were diagnosed with stage III, and 6.5% of surgically resectable cases were found to be unresectable at laparoscopy, with a 93.5% true positive. To assess resectability, the diagnostic utility revealed that laparoscopy had 93.6% sensitivity, 100% specificity, 77.8% NPV, and 100% PPV with an accuracy of 94.7%.Serous cystadenocarcinoma was the most common histopathology type in 24(63.15%) patients. The OS during the observation period was 26.8 months ±1.1 (CI: 24.6–29.0). The estimated DFS was 9.15 months for all patients, 10 months for 25% of patients, and 8 months for 75% of patients. The RFS was 9.56 months. Conclusion: Diagnostic laparoscopy has effective feasibility and great efficacy when added to the conventional initial diagnostic workup in predicting optimum resectability of ovarian cancer.